Characterization of fermentation liquid from mangrove leaves Avicennia marina and its inhibitory potential for bacterium causing ice-ice disease - Samsu Adi Rahman; Sukenda; Widanarni; Alimuddin; Julie Ekasari (Jurnal Akuakultur Indonesia)
ABSTRACT